Environmental ethics in Islamic Civilization: Interaction with Animals - Zeinab Fazli; Zahra Alhooii Nazari (اخلاق وحیانی, 2022)
Environmental crises and the danger of extinction of various and rare animal species have affected many societies, including Islamic societies. One of the most important issues leading to these crises is due to the hegemonic approach of man and modern civilization to nature and its manifestations such as animals. What is surprising is that Muslims in the past of their civilization, based on their original religious and ideological values and values, have made a sincere effort to protect the environment and treat animals very progressively. For Islam and Muslims, nature was the manifestation of divine craft, and respect for its manifestations, including animals, was the duty of every Muslim. Hence, a special environmental ethic was formed in Islamic civilization that evoked in the Muslim person a sense of respect and affection for animal life. The practical result of this cultural-civilizational approach was a certain way of interacting with animals, the treatment of which was accompanied by compassion and kindness to animals, these companions of human earth travel, and friendship and tolerance with them until they reached the divine carpenter.